Historical hypotheses of chimpanzee tool use behaviour in relation to natural and human-induced changes in an East African rain forest - Thibaud Gruber (Revue de Primatologie)
Chimpanzees and humans have co-existed in Africa for millennia. The forests inhabited by chimpanzees have experienced numerous changes in recent time, most notably during the last 12,000 years, as the current interglacial age started. In this article, I will study the case of Western Ugandan forests to describe the different factors, natural and human-induced, which affect a tropical forest, and draw hypotheses on the influence of these changes on chimpanzee cultural behaviour. Before colonial times, the Budongo Forest was shaped by elephant migrations and fires lit by the pastoralists who settled in the area. Later on, the British colonial power organized the exploitation of the forest through work plans aimed at insuring sustainable extraction of valuable timber. The human activity resulted in unexpected consequences in the forest. Interestingly, the resident chimpanzees are nowadays remarkable in the small size of their tool use repertoire. Ecological analysis and tool use observations in Uganda only support partly the opportunity and necessity hypotheses that are currently proposed to explain the influence of ecological factors on tool-using behaviour. Rather, the data I present here suggest that the temporal dimension of ecological changes in the forest must be taken into account to explain tool use behaviour variation in Ugandan forests. I propose a dynamic model connecting the necessity and opportunity factors influenced by ecological changes over time, most salient in Ugandan forests through the variability in food diversity. Finally, I conclude on the ever-changing ecological situation in Budongo Forest.